Validity and reliability of ICT utilization and technological beliefs instrument for teachers - Masood, Mastini; Mahmud, Rosnaini; Wan Ali, Wan Zah; Nawawi, Mokhtar (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
The aim of this paper is to disseminate findings related to the validity and reliability of the instruments to measure the utilization of Information and Communication Technology (ICT) and Technological Beliefs among expert teachers. The instrument was developed based on literature review and existing measurements. The instrument consisted of 77 Likert scale items measuring demographic information, technological beliefs (teacher beliefs toward the use of ICT in teaching and learning) and ICT utilization from the aspects of general, exploration, and social and communication uses. The instrument was validated by two Educational Technology experts, whereas reliability was obtained through a pilot study involving 32 expert teachers from seven secondary schools. Based on the pilot study, the reliability of the ICT utilization scale was 0.94, while for the ICT utilization scale 0.943. This finding demonstrates that the instrument has content validity and reliability to measure ICT utilization and technological beliefs among expert teachers.